Secondary Surgical Cytoreduction for Recurrent Ovarian Cancer. Issue 3 (March 2020) - Coleman, Robert L.; Spirtos, Nick M.; Enserro, Danielle; Herzog, Thomas J.; Sabbatini, Paul; Armstrong, Deborah K.; Kim, Jae-Weon; Park, Sang-Yoon; Kim, Byoung-Gie; Nam, Joo-Hyun; Fujiwara, Keiichi; Walker, Joan L.; et al.
Abstract : (Abstracted from N Engl J Med 2019;381:1929–1939) The National Comprehensive Cancer Network recommends secondary cytoreduction for ovarian cancer patients with recurrent disease who have received no treatment for a period of 6 months following a complete response from prior chemotherapy. Retrospective reviews and meta-analyses have shown the most benefit from this operation in those with platinum-sensitive disease and those with little or no postoperative residual disease.